Local governance, corruption, and public service quality: evidence from a national survey in Vietnam. Issue 2 (6th March 2017) - Nguyen, Thang V.; Bach, Thang N.; Le, Thanh Q.; Le, Canh Q.
Abstract : Purpose: The purpose of this paper is to examine whether higher levels of transparency, accountability, and participation have a statistically significant association with corruption, and whether corruption is highly correlated with lower public service quality in the context of Vietnam's transition economy. Design/methodology/approach: Using individual-level survey data from Vietnam Provincial Governance and Public Administration Performance Index, the research employs an ordered probit model to test whether greater transparency, accountability, and participation is associated with lower levels of corruption. Moreover, district-level data are used to test the relationship between corruption and quality of public services particularly in healthcare and primary education. Findings: Results show that a higher level of transparency, participation, and accountability is associated with a lower level of corruption, and that corruption is negatively associated with public service quality. Research limitations/implications: The use of cross-sectional data does not allow the establishment of causal relationships among variables. Practical implications: The research suggests that fostering accountability to citizens and non-state sectors and promotion of genuine participation from these actors are critical for the future anti-corruption agenda. Originality/value: In developing countries, whether corruption enhances efficiency of service provision is highly debatable. This research contributes to this debate by suggesting that corruption significantly decreases the quality of public service, and that improving local governance helps reduce corruption.